THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND THERAPEUTIC COMMUNICATION FOR INPATIENT NURSES AT KUNINGAN MEDICAL CENTER LURAGUNG GENERAL HOSPITAL IN 2023 - Endangsari, Linda Ayu; Peraten pelawi, Arabta M.; Rotua Suriany Simamora (Rena Cipta Mandiri, 2023)
Background: In recent years, the growth and development of hospitals has greatly increased, especially in the city of Kuningan. Private hospitals and state hospitals were built everywhere. So that it will lead to intense competition for them and pose challenges for the hospital itself. Starting from workers, nurses, experts in the health sector and others. In addition to the facilities provided by the hospital to patients, the hospital also has the task of carrying out efficient and successful health efforts by prioritizing the healing and recovery process for hospital patients. refer to the patient. One area that can provide quality services to patients is the nurse. Research Objectives: Knowing